An Adolescent Boy with Acquired Epileptic Aphasia - Landau Kleffner Syndrome: A rare case report - Sharma, SR; Sharma, N; Yeolekar, ME (Journal of Nepal Paediatric Society, 2011)
A 13 year adolescent boy presented with complaints of progressive loss of speech and seizure disorder for the past 1 year. The boy was developmently normal before the onset of illness. There was history of subtle trauma to head. He started communicating with signs followed by paucity of speech progressed to complete aphasia and abnormal behavior in the form of burst of aggressiveness and hyperactivity. Boy had partial, generalized tonic-clonic seizures occurred during sleep. Mental status examination revealed abnormal behaviour, attention deficits, auditory agnosia and aphasia (both expressive and receptive). All relevant investigations including BERA were normal. EEG showed repetitive spikes and wave activity in bilateral parietooccipital regions during nonrapid eye movement. Clinical features and EEG led to a diagnosis of Landau Kleffner Syndrome. He was started on Lamotrigine, steroid and speech therapy. The boy started showing improvement of symptoms in form of understanding of short sentences. Key words: Landau Kleffner Syndrome; EEG; Seizures DOI: 10.3126/jnps.v31i1.3543 J Nep Paedtr Soc 2010;31(1):57-60